2004
DOI: 10.1590/s0074-02762004000300012
|View full text |Cite
|
Sign up to set email alerts
|

Virulence markers and antimicrobial susceptibility of bacteria of the Bacteroides fragilis group isolated from stool of children with diarrhea in São Paulo, Brazil

Abstract: lead and nickel. Plasmids of 2.9, 4.4, 4.8, and 8.9 kb were observed in 6 tested strains. These results show the values of the species identification from clinical infections, as well as of the periodic evaluation of the resistance patterns of the B. fragilis group at Brazilian medical institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
(37 reference statements)
1
13
2
2
Order By: Relevance
“…Studies performed in recent years reported cefoxitin resistance in BFG bacteria to be 6,8%-33,3% in Europe, 12,6% in Canada, 23% in Brasil, 6,1% in Argentina [7,8,20,21]. In this study, in clinical isolates cefoxitin resistance was found as 28% and in intestinal isolates as 32%, which is similar to the rates reported from the European countries.…”
Section: Statistical Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Studies performed in recent years reported cefoxitin resistance in BFG bacteria to be 6,8%-33,3% in Europe, 12,6% in Canada, 23% in Brasil, 6,1% in Argentina [7,8,20,21]. In this study, in clinical isolates cefoxitin resistance was found as 28% and in intestinal isolates as 32%, which is similar to the rates reported from the European countries.…”
Section: Statistical Resultssupporting
confidence: 86%
“…Clindamycin resistance in BFG bacteria is an arising problem and the resistance rates from various countries are reported between 24% and 56% [ 2,5,7,8,21,28]. High level resistance to clindamycin in BFG bacteria is mediated by 23S rRNA methylase coded by different erm M A N U S C R I P T…”
Section: Statistical Resultsmentioning
confidence: 99%
“…Além disso, tal espécie é considerada patógeno oportunista em humanos, com a capacidade de causar infecções na cavidade peritoneal e levar à formação de abscessos quando ocorre um trauma, por exemplo, no sítio de colonização. A espécie B. fragilis apesar de minoritária na microbiota intestinal, é a mais frequentemente associada a processos infecciosos, tais como bacteremias, infecções intraabdominais, abscessos e infecções em tecidos moles (Nakano et al, 2004).…”
Section: Resultsunclassified
“…Outra bactéria foco deste trabalho é pertencente ao gênero Bacteroides, à espécie B. fragilis avaliada apesar de minoritária na microbiota intestinal, é a mais frequentemente associada a processos infecciosos, tais como bacteremias, infecções intra-abdominais, abscessos e infecções em tecidos moles (Nakano et al, 2004).…”
Section: Introductionunclassified
“…Nakano and Avila-Campos (2004) reported in a study performed on stools of 15 children with diarrhea the isolation of 64 B. fragilis group strains of which 39 were B. fragilis , 8 B. vulgatus , 6 B. uniformis , 6 P. distasonis and 5 B. ovatus . In our study we isolated a single strain of B. fragilis in diarrheal stool of a person older than 54 years (74 years).…”
Section: Discussionmentioning
confidence: 99%